Temperature sensation in Parkinson's disease measured by quantitative sensory testing: a single-center, case-control study - Kaiserova, Michaela; Kastelikova, Anetta; Grambalova, Zuzana; Otruba, Pavel; Zapletalova, Jana; Mensikova, Katerina; Rosales, Raymond; Kanovsky, Petr (International Journal of Neuroscience, 2023)
BACKGROUND: The pathophysiology of abnormal temperature sensation in Parkinson's disease (PD) remains unclear. Abnormal thermal detection does not seem to depend on the dopaminergic deficit, suggesting that other systems play a role in these changes, probably both central and peripheral. METHODS: We measured thermal detection thresholds (TDT) using quantitative sensory testing (QST) in 28 patients with PD and compared them with 15 healthy controls. RESULTS: Of 28 patients, 21% had increased TDT according to the normative data. TDT were higher on the dominant side. No correlation between TDT and disease duration, severity of motor impairment, and dopaminergic therapy was observed. 50% of the patients had difficulty differentiating between warm and cold stimuli, as TDT were within the normal range in most of these patients. CONCLUSIONS: Twenty-one percent of the patients in our study had increased TDT according to the normative data. Abnormal thermal detection was more pronounced on the dominant side. Abnormal differentiation between the thermal stimuli suggest impaired central processing of thermal information.
Keywords: Sensation; Cold Temperature; studie případů a kontrol; čití, cítění; lidé; Parkinson Disease; teplota; Case-Control Studies; Parkinsonova nemoc; Humans; nízká teplota; Temperature